2005
DOI: 10.1021/ie050532u
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recovery of Gold by Novel Lignin-Based Adsorption Gels

Abstract: Three different kinds of adsorption gels, viz., cross-linked lignophenol, cross-linked lignocatechol, and crosslinked lignopyrogallol, were prepared by the chemical modification of wood lignin. The adsorption behaviors of these gels for Au(III) along with some other metals were studied and compared to that of activated carbon. All three gels were found to be more selective for Au(III) than activated carbon with comparable adsorption capacities. Of the lignin gels, cross-linked lignophenol exhibited the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 8 publications
4
39
1
2
Order By: Relevance
“…The next generation of cellulosic ethanol is being developed from these polysaccharides with microbial fermentation [3,4]. Lignin, a phenolic polymer, is also an important source for industrial applications such as adhesive resin [5,6] and lignin gels [7,8]. Lignin and cellulose are being developed for the synthesis of biodegradable polymers [9].…”
Section: Introductionmentioning
confidence: 99%
“…The next generation of cellulosic ethanol is being developed from these polysaccharides with microbial fermentation [3,4]. Lignin, a phenolic polymer, is also an important source for industrial applications such as adhesive resin [5,6] and lignin gels [7,8]. Lignin and cellulose are being developed for the synthesis of biodegradable polymers [9].…”
Section: Introductionmentioning
confidence: 99%
“…and Zn(II) were not adsorbed by the gel. In our previous study crosslinked lignophenol gel was found to be able to adsorb only Au(III) [7][8][9]. The aminated lignophenol gels EN-lignin and PA-lignin have shown some affinity also for Pd(II) and Pt(IV).…”
Section: Kinetics Of Adsorptionmentioning
confidence: 91%
“…Untuk tujuan ini sejumlah reagen ekstraksi pelarut, penukar ion dan adsorben telah disintesis. Akan tetapi saat ini kecenderungan penelitian recovery emas telah bergeser dari bahan sintetik ke bahan alam seperti bio-degradable polimer yaitu kitosan [4], persimmon tannin [5], dan turunan lignin [6].…”
Section: Pendahuluanunclassified